Crystal structure of new phosphates Ca9–xPbxEu(PO4)7 from Rietveld refinement. (23rd April 2015) - Deyneko, Dina; Stefanovich, Sergey; Lazoryak, Bogdan
Abstract : New phosphates Ca9– x Pb x Eu(PO4 )7 were obtained by solid state reaction techniques at 1213–1253 K in air atmosphere and were found to be isotypic with whitlockite-type β -Ca3 (PO4 )2 . The unit cell parameters were determinate using Le Bail decomposition. Rietveld method structural refining showed that Eu 3+ ions are located statistically with calcium in M 1, M 2, and M 3 sites, whereas Pb 2+ -ions are preferentially located in the M 3. Examination of optical second harmonic generation evidences nonlinear optical activity and confirms polar space group R 3 c .